(untitled) (Bangladesh Journal of Agricultural Research, 2014)
Improper doses and splits of nitrogenous fertilizer are two major constraints achieving higher yield of transplanted aman rice in Bangladesh. A field experiment was carried out to study the effect of different levels and split application of nitrogen (N) fertilizer on yield and yield attributes of transplanted aman rice (var. BRRI dhan30). The experiment was laid out in a split-plot design with four split levels of N : T1 [? N a t b asal + ? N a t 2 5 d ays a fter transplanting (DAT) + ? N at 50 DAT ], T2 [½ N at 25 DAT + ½ N at 50 DAT], T3 [? N at 15 DAT + ? N at 30 DAT + ? N at 45 DAT], T4 [¼ at N 15 DAT + ½ N at 30 DAT + ¼ N at 45 DAT] in the main plot and four levels of N in the sub-plot: control (0 kg N/ha), N1 (40 kg N/ha), N2 (80 kg N/ha), and N3 (120 kg N/ha). Data collected were total tillers/hill, effective tillers/hill, number of grains/panicle, grain yield (t/ha), biological yield (t/ha) as well as some other morphological characters. Among the N splits, treatment T3 produced highest total tillers/hill (16.45), effective tillers/hill (12.73), panicle length (24.97 cm), grains/panicle (127.92), grain yield (5.53 t/ha), biological yield (12.87 t/ha), and harvest index (42.79%). Among the N levels, treatment N3 produced highest total tillers/hill (16.50), effective tillers/hill (12.69), grains/panicle (130.36), grain yield (5.40 t/ha), and biological yield (12.66 t/ha). Conversely, the treatment combination of N3 and T3 produced the highest value for most of the traits evaluated, namely total tillers/hill (18.03), effective tillers/hill (14.97), grains/panicle (137.48), grain yield (5.77 t/ha), biological yield (13.08 t/ha), and harvest index (44.10%). Hence, the treatment combination of N3 and T3 is suggested to bring higher economic benefit from transplanted aman rice in the study area. DOI: http://dx.doi.org/10.3329/bjar.v38i4.18886 Bangladesh J. Agril. Res. 38(4): 579-587, December 2013